POL-PAVTI reportPOL-PAVTI – Polish report on transcatheter pulmonary artery valve implantation of Melody-Medtronic prosthesis in the first 14 patients in Poland - Rużyłło, Witold; Demkow, Marcin; Włodarska, Elżbieta K.; Kowalski, Mirosław; Śpiewak, Mateusz; Siudalska, Hanna; Wolski, Piotr; Miśko, Jolanta; Hoffman, Piotr; Kusa, Jacek; Szkutnik, Małgorzata; Białkowski, Jacek; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Aim: To assess the early results of the pulmonary artery valve transcatheter implantation (PAVTI) in pts included into POL-PAVTI registry. Detailed medical and economic analyses were performed. Methods: Pulmonary artery valve implantation was performed in 14 pts (9 men), aged 16-31 (×– 24.6 ± 4.8) years, with pulmonary homograft dysfunction after total repair of tetralogy of Fallot (4 pts), pulmonary atresia (2 pts), pulmonary stenosis (1 pt), common arterial truncus type I (1 pt), Ross procedure (3 pts) and TGA – Rastelli operation (3 pt). Eleven pts underwent in the past 2-5 surgical or/and catheter interventions. Indication for PAVTI was based on clinical evaluation and echocardiographic studies. Assessment of morphological and functional features of the right ventricle (RV) and homograft with the use of cardiac magnetic resonance (CMR) was performed in 10 cases. Pulmonary stenosis (max. pulmonary gradient 32-119, ×– 72 ± 28 mm Hg) was observed in 13 pts and/or significant pulmonary regurgitation in 10 pts. The procedure was performed in general anesthesia. The deployment of a valved stent in the pulmonary valve position was preceded by a metal stent implantation. Results were evaluated by echocardiography two days after the procedure and one month later. Four patients were evaluated 6 months after procedure. Results: Time of the procedure varied 60-190 (×– 127 ± 35) min, time of fluoroscopy ranged 12-31 (×– 21 ± 11) min. PAVTI was successfully performed in all pts without serious complications. Patients were discharged from the hospital 48-293 (×– 120 ± 71) h after procedure. Significant reduction of pulmonary gradient after the procedure assessed by echocardiography was observed on the second day (20-60, ×– 38 ± 12 mm Hg, p < 0.0001) and one month (19-52, ×– 34 ± 9 mm Hg, p < 0.0001). Mild pulmonary regurgitation was observed in 2 pts. In 4 pts evaluated 6 months after procedure haemodynamic parameters were unchanged; no late complications were observed. Average cost of the procedure including a price of the valve (82 000 PLN) was 98 000 PLN. Conclusions: Pulmonary artery valve transvascular implantation is an effective and safe method of non-surgical treatment for patients with homograft dysfunction. Cost-effectiveness is approvable.